Comprehensive Review on the Genus Haloxylon: Pharmacological and Phytochemical Properties - Amtaghri, Smail; Eddouks, Mohamed (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Aims: This review aimed to review the biological, pharmacological, and phytochemical aspects of the genus Haloxylon. Background: Plants of the genus Haloxylon have been used for a long time in traditional medicine, and they are distributed in the western Mediterranean region to the Middle East, Iran, Mongolia, Burma, and southwest China. The studied parts of Haloxylon species include aerial parts, leaves, branches, seeds, roots, rhizosphere, soil, and whole plants, used to treat several diseases, including sexual disorders, hepatobiliary disorders, eye disorders, skin diseases and hemorrhoids, diarrhea, and effective in the treatment of various ailments such as snake bite, stomach ache, diabetes, wounds, earache and sciatica pain, windbreak dune fixation, feeding of livestock and firewood. Objectives: Till now, no review on the genus Haloxylon has been conducted. This review aimed to provide updated information on the genus Haloxylon, including traditional medicinal uses, valorization and exploitation of medicinal plants, phytochemistry, botanical characterization, pharmacological and toxicological research focusing on the medicinal properties of several Haloxylon species, especially their antioxidant, antibacterial, anti-inflammatory, cytotoxic and antifungal activities, as well as the effect of each bioactive molecule isolated from these species and their pharmacological use, including the preclinical evaluation of new drugs. Materials and Methods: The present work was conducted using various scientific databases, including Science Direct, Scopus, PubMed, Google Scholar, etc. Correct plant names were verified from plantlist.org. The results of this search were interpreted, analyzed, and documented based on the obtained bibliographic information. Results: Among all species of the Chenopodiaceae family, 6 species of the Haloxylon genus have approved antioxidant activity, 5 species have antibacterial activity, 3 species have anti-inflammatory activity, 2 species have cytotoxic activity, and 3 species have antifungal activity. The majority of the chemical constituents of this plant include flavonoids, alkaloids, phenols, saponins, glycosides, and tannins. Among them, the main bioactive constituents would be present in the alkaloid fraction. The study of more than 9 Haloxylon plants has identified more than 46 compounds. Pharmacological research proved that crude extracts and some pure compounds obtained from Haloxylon had activities for the treatment of different diseases. The objective of the present study was focused on antioxidant, antibacterial, anti-inflammatory, cytotoxic and antifungal diseases. From the study of the phytochemistry of the Haloxylon family, it was concluded that all studied plants had active compounds. Among them, 11 isolated molecules have medicinal activities with antioxidant properties, 10 molecules showed antibacterial effects, more than 6 molecules have anti-inflammatory properties, more than 9 isolated molecules have medicinal activities against cytotoxic diseases, and more than 28 molecules have antifungal effects. Therefore, the safety of Haloxylon herbal medicine should be considered a top priority in the early stages of development and clinical trials. Conclusion: Several previously conducted studies have validated multiple traditional uses of Haloxylon species. Further research is needed on Haloxylon plants before they can be fully utilized in the clinic as a potent drug candidate, as researchers are mainly focusing on alkaloids, diterpenoids, and triterpenoids, whereas there are many other types of compounds that may possess novel biological activities.
Keywords: traditional use